1988
DOI: 10.1002/ijc.2910420515
|View full text |Cite
|
Sign up to set email alerts
|

Relations between ph, oxygen partial pressure and growth in cultured cell spheroids

Abstract: The pH gradients, oxygen partial-pressure gradients and growth curves were measured for 7 different types of spheroids. Growth curves were measured in liquid overlay culture and thereafter the spheroids were attached to cover glasses and transferred to a chamber for micro-electrode measurements. The spheroids were randomly divided for pH or pO2 measurements which then were made under conditions as identical as possible. The decreases in pO2 and pH, delta pO2 and delta pH were calculated as the difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 23 publications
5
100
0
2
Order By: Relevance
“…The fit to the model was less satisfactory when the binding parameters for pH 6.7 or 7.6 were used, indicating that the estimate of pH 7.2 may be reasonable. This is also supported by microelectrode data showing a pH gradient from 7.4 to 7.1 through the viable rim of V79-379A spheroids (Carlsson and Acker, 1988). The other parameters not defined with precision are the intracellular volume fraction in the MM, the fraction of necrotic tissue, and the distribution of thicknesses for each MM.…”
Section: Diffusion Of [3h]dapa Through V79-171 B MMmentioning
confidence: 60%
“…The fit to the model was less satisfactory when the binding parameters for pH 6.7 or 7.6 were used, indicating that the estimate of pH 7.2 may be reasonable. This is also supported by microelectrode data showing a pH gradient from 7.4 to 7.1 through the viable rim of V79-379A spheroids (Carlsson and Acker, 1988). The other parameters not defined with precision are the intracellular volume fraction in the MM, the fraction of necrotic tissue, and the distribution of thicknesses for each MM.…”
Section: Diffusion Of [3h]dapa Through V79-171 B MMmentioning
confidence: 60%
“…pO2 pH-gradients to cellular metabolism has been measurements in HT29 spheroids revealed steep investigated intensively in HT29 human colon p 0 2 gradients with pOz decreases between spheroid carcinoma tumor cells and U118MG human malign Figure 2 demonstrates the frequence distribution of p 0 2 and pH values of HT29 and U 118 MG MS with the significant differences in the mean p 0 2 and pH. High lactate production in Ull8MG spheroids in contrast to HT29 spheroids with a high oxygen consumption has been described by Carlsson and Acker (1988) confirming the measured pOa -and pH-gradients. The findings of Figure 2 are in also in agreement with higher oxidative metabolic activity monitored in HT29 cells and high LDH activity measured in U118MG spheroid homogenates as estimated by the incorporation rates of 1 -and 2-14C pyruvate (Gorlach et al 1995).…”
Section: The Model (Cell Cycle Characteristics Glucosementioning
confidence: 87%
“…Interestingly, large tumor spheroids were slightly more susceptible towards hyperthermia treatment, which may be due to the more acidic tissue microenvironment in large as compared to small tumor spheroids. 45,46 It has been previously shown that low intracellular pH increases the thermosensitivity of mammalian cells, 47 and it was suggested that experimental lowering of the intracellular pH by blocking of cellular pH regulation in combination with hyperthermia may be a useful way to eliminate radioresistant hypoxic cells in tumor tissues. 48 The data of our study clearly demonstrate that hyperthermia treatment resulted in a robust increase in P-glycoprotein expression in small drug-sensitive tumor spheroids on the transcriptional as well as on the translational level, whereas only moderate increase was observed in large tumor spheroids that are characterized by high intrinsic levels of P-glycoprotein and a MDR phenotype.…”
Section: Discussionmentioning
confidence: 99%